Finance's Social License? Sugar, Farmland and Health - Kiah Smith; Geoffrey Lawrence (Kerman University of Medical Sciences, 2021)
Background  This paper examines the exclusion of public health from social license narratives within an increasingly financialised food system, through a case study of foreign ownership in the Australian sugar industry. As finance actors such as asset management firms, pension funds, private equity funds, state owned enterprises and sovereign wealth funds engage in speculative farmland investment, commodity futures trading, and the conversion of farmland into a financial asset, power within agro-industrial food supply chains becomes increasingly concentrated. This has been associated with increased food prices and more processed food, contributing to obesogenic diets, hunger, and poorer health outcomes for many. The potential for negative social and environmental impacts has prompted awareness of the need for financial actors to demonstrate sustainability, responsibility and accountability in their farmland investments.  Methods  This paper uses thematic analysis of qualitative interviews and key documents to assess four recent acquisitions of sugarcane land in North Queensland. We consider how companies' efforts to establish or maintain a social license to operate (SLO) intersect with their capital accumulation strategies. Results Our findings demonstrate that the link between the commodification of 'unhealthy' food inputs (such as sugar) and financialisation remains outside the purview of financiers. Instead, agribusiness firms use narratives centred on biofuels investment and energy/food security to justify their legitimacy in the sugar sector. We organise our findings according to two 'narratives:' constructing trust and credibility through ethical compliance; and, biofuels expansion as a legitimate response to climate change. The concept of social license is much stronger in the second narrative, but health is largely missing.  Conclusion  The 'distancing' between responsibility and health outcomes highlights the limits to principles of responsible financial investment, and to the legitimacy of finance to claim an SLO - the ongoing approval and acceptance by society to conduct its activities.